2022
DOI: 10.1002/anie.202216315
|View full text |Cite
|
Sign up to set email alerts
|

Overall Carbon‐neutral Electrochemical Reduction of CO2 in Molten Salts using a Liquid Metal Sn Cathode

Abstract: An overall carbon-neutral CO 2 electroreduction requires enhanced conversion efficiency and intensified functionality of CO 2 -derived products to balance the carbon footprint from CO 2 electroreduction against fixed CO 2 . A liquid Sn cathode is herein introduced into electrochemical reduction of CO 2 in molten salts to fabricate core-shell SnÀ C spheres (Sn@C). An in situ generated Li 2 SnO 3 /C directs a selftemplate formation of Sn@C. Benefitting from the accelerated reaction kinetics from the liquid Sn ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…[ 1‐3 ] Photocatalytic CO 2 reduction is closely related to the photoinduced carrier migration kinetics. [ 4‐7 ] However, before reaching surface, most electron‐hole pairs are firmly bound through Coulombic interactions as excitons or undergo strong radiative recombination. Bulk configuration usually determines excitonic effects.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…[ 1‐3 ] Photocatalytic CO 2 reduction is closely related to the photoinduced carrier migration kinetics. [ 4‐7 ] However, before reaching surface, most electron‐hole pairs are firmly bound through Coulombic interactions as excitons or undergo strong radiative recombination. Bulk configuration usually determines excitonic effects.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Molten salt electrolysis has a solid foundation in industrial extraction of active metals, and is recently demonstrated as a promising method to convert CO 2 into advanced energy materials for an overall carbon-neutral utilization of CO 2 . [4][5][6][7][8] Electrolytic aluminum industry as the most mature application of molten salt electrochemical metallurgy process outputs over 40 million metric tons Al in 2022 in China. [9] Using excess capacity of electrolytic aluminum industry to electrolyze industrial CO 2 emission can not only reduce carbon emission but also relieve the pressure of production regulations.…”
Section: Introductionmentioning
confidence: 99%
“…Solar‐driven electrochemical CO 2 reduction hence holds promise for artificial photosynthesis. Molten salt electrolysis has a solid foundation in industrial extraction of active metals, and is recently demonstrated as a promising method to convert CO 2 into advanced energy materials for an overall carbon‐neutral utilization of CO 2 [4–8] . Electrolytic aluminum industry as the most mature application of molten salt electrochemical metallurgy process outputs over 40 million metric tons Al in 2022 in China [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Considering the depth of the overall synthesis strategies, the major focus is limited only to the chemical methods, including chemical vapor deposition, 17 the hydrothermal process, 18–20 pyrolysis of organic carbon precursors, 21,22 and salt-assisted synthesis. 23–26 The advantages of chemical methods over hard physical ones are demonstrated by their ease in synthesis, high reproducibility, high yields and fewer defects in carbon morphologies. Of the various chemical synthesis pathways, hydrothermal methods belong to wet-chemical processes, which require the precursors, such as glucose, to have abundant solubility in water.…”
Section: Introductionmentioning
confidence: 99%